TAX LAW IMPLEMENTATION ON CRYPTOCURRENCY TRANSACTIONS: A GLOBAL PERSPECTIVE - Wahyuni, Fitri (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
In today's digital era, cryptocurrency has emerged as a new form of asset that challenges traditional financial and tax law paradigms. This article aims to analyze how various countries around the world apply tax laws to cryptocurrency transactions, focusing on the comparison of regulatory approaches and their economic and social implications. Through a comparative analysis methodology and case studies, this research reveals the diversity in cryptocurrency tax regulations, highlighting significant policy differences between countries. The main findings indicate that despite efforts to harmonize cryptocurrency tax regulations globally, there is still significant non-uniformity, impacting economic policy and social justice. This article also explores the challenges faced by tax authorities in identifying, tracking, and taxing cryptocurrency transactions, and discusses the potential of cryptocurrencies in enhancing the efficiency and transparency of the tax system. The conclusions of this study offer policy recommendations for governments and tax authorities in addressing the unique challenges posed by cryptocurrencies, as well as suggesting directions for future research in this field.